Aerospace series. Screws 100° countersunk normal head, offset cruciform recess, coarse tolerance normal shank, long thread, in alloy steel, cadmium plated. Classification: 1 100 MPa (at ambient temperature) / 235 °C. (31st March 2016) - British Standards Institution,
No abstract available